2003
DOI: 10.1088/0022-3727/36/20/023
|View full text |Cite
|
Sign up to set email alerts
|

Electrohydrodynamics and dielectrophoresis in microsystems: scaling laws

Abstract: The movement and behaviour of particles suspended in aqueous solutions subjected to non-uniform ac electric fields is examined. The ac electric fields induce movement of polarizable particles, a phenomenon known as dielectrophoresis. The high strength electric fields that are often used in separation systems can give rise to fluid motion, which in turn results in a viscous drag on the particle. The electric field generates heat, leading to volume forces in the liquid. Gradients in conductivity and permittivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
694
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 620 publications
(716 citation statements)
references
References 23 publications
21
694
0
1
Order By: Relevance
“…Similar to those previously studied in eDEP [34][35][36][37][38][39][40][41][42][43][44][45][46][47], electrothermal flows in iDEP devices also arise from the action of the electric field (both DC and AC) on fluid inhomogeneities (predominantly electrical properties including conductivity and permittivity) formed in the constriction region due to Joule heating-induced temperature gradients. Figure 4 shows the numerically predicted temperature and electric field contours in the constriction region at 100 V DC/500 V AC.…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…Similar to those previously studied in eDEP [34][35][36][37][38][39][40][41][42][43][44][45][46][47], electrothermal flows in iDEP devices also arise from the action of the electric field (both DC and AC) on fluid inhomogeneities (predominantly electrical properties including conductivity and permittivity) formed in the constriction region due to Joule heating-induced temperature gradients. Figure 4 shows the numerically predicted temperature and electric field contours in the constriction region at 100 V DC/500 V AC.…”
Section: Resultssupporting
confidence: 63%
“…It has been long known in capillary electrophoresis that Joule heating can elevate the buffer temperature and disturb the electroosmotic flow causing significant sample dispersion [30][31][32][33]. The effects of Joule heating on fluid temperature and motion in eDEP have been investigated previously [34][35][36][37][38]. It was reported that a pair of counter-rotating fluid circulations could form near the microelectrodes [39].…”
Section: Introductionmentioning
confidence: 99%
“…Force generated through DEP is dependent upon an induced rather than an intrinsic dipole, so it does not require a particle having a net (nonzero) charge [37]. There are multiple models representing the dipole moment in various frequency regimes [38,39], but the classical electrostatic Maxwell-Wagner high frequency model for spherical particles will be framed here [40].…”
Section: Theory Of Dielectrophoresismentioning
confidence: 99%
“…In order to manipulate particles and cells by utilizing DEP, the magnitude of the DEP force should be large enough to dominate other forces such as drag force, electrothermal forces, buoyancy force, alternating current electroosmotic force and the Brownian motion. Therefore, the order of magnitude estimate of the various forces experienced by a particle is crucial for DEP-based applications to predict the resultant motion of the particles (detailed analysis of the scaling of the various forces with system parameters can be found elsewhere [39,40]). Considering the length scale of the present design and the length scale of the particles to be used, only the effects of the DEP and drag forces are included in the analysis.…”
Section: Introductionmentioning
confidence: 99%